On the Relationship of Information Processes and Asset Price Processes - Erik Lüders; Bernhard Peisl (University of Konstanz, Center of Finance and Econometrics (CoFE), 2000)
Asset price processes are completely described by information processes and investors preferences. In this paper we derive the relationship between the process of investors expectations ofthe terminal stock price and asset prices in a general continuous time pricing kernel framework. To derive the asset price process we make use of the modern technique of forward-backward stochastic differential equations. With this approach it is possible to show the driving factors for stochastic volatility of asset prices and to give theoretical arguments for empirically well documented facts. We show that stylized facts that look at first hand like financial market anomalies my be explained by an information process with stochastic volatility.
urn:nbn:de:bsz:352-opus-4232
Keywords: 330; Börsenkurs; Volatilität; Informationsverhalten; Erwartungstheorie; Stochastischer Prozess; Theorie